ERISE: A Web-Based Learning System for Digital Records Management in Vocational High Schools - Sutirman Sutirman; Yuliansah Yuliansah (Dinamika Pendidikan, 2025)
This study aims to develop the Electronic Record Information System for Education (ERISE) as a learning medium to accommodate practical learning of digital archive management at VHS OMBS. The research employed a Research and Development (R&D) method using the Richey & Klein model, consisting of three phases: design, development, and evaluation. The respondents in this study were 14 individuals, comprising seven teachers, five archival practitioners, and two media experts. Data were collected using questionnaires, focus group discussions (FGDs), and interviews, with instruments including a 5-point Likert-scale questionnaire, FGD guidelines, and interview protocols. Data were analyzed descriptively, with raw scores converted to a 5-point scale and the minimum media feasibility category set at a “B” rating. The results indicate that (1) the ERISE application has been developed as a web-based learning system for digital archive management practice by the needs analysis, design, and development stages; and (2) the feasibility test yielded an average score in the “Very Good” (“A”) category. This learning medium is expected to make a concrete contribution to enriching vocational practice, particularly by facilitating the entire archiving process starting from receipt, recording, distribution, classification, retention, and digital signatures.